Vpliv načina življenja na omilitev negativnih učinkov vsakodnevnega dolgotrajnega sedenja - Jakše, Boštjan (Šport (Ljubljana), 2017)
Current studies show that prolonged daily sitting leads to important negative consequences on health and the mortality of people. The analyses of different researches have also shown that regular several-hours-long exercise cannot replace the negative effects of prolonged daily sitting at work, at home, in front of the television, in school, on transport vehicles, and during leisure activities on all-cause mortality. Numerous experts have therefore studied different strategies for mitigating daily sitting and discovered that society, the employer, and the individual have various options when facing the consequences of a modern way of life, which not only includes prolonged daily sitting but also physical inactivity, unhealthy nutrition, and other deviant behaviour. The purpose of this article is to present in detail the problem of negative effects of prolonged daily sitting and different ways of its mitigation. For most people, practical solutions are represented by various measures in sedentary jobs, physical activity in one's free time, a healthy nutrition, and - in general - a healthy life style. The latter also includes a controlled alcohol and salt intake, absence of smoking, adequate sleep and an appropriate response to stressful situations.
Keywords: dolgotrajno sedenje; healthy nutrition; mortality; physical activity; prolonged sitting; sport; šport; telesna dejavnost; umrljivost; zdravje; zdravo prehranjevanje